Selection of common bean lines with high agronomic performance and high calcium and iron concentrations - Ribeiro, Nerinéia Dalfollo; Domingues, Lucas da Silva; Zemolin, Allan Emanoel Mezzomo; Possobom, Michele Thaise Della Flora (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the genetic variability of common bean lines for cycle, weight of 100 grains, grain yield, cooking time, and grain calcium and iron concentrations. Twenty‑four common bean lines were evaluated in two crop cycles (2010 and 2011). The ¯Z index was used for the selection of superior lines for most of the traits. The DF 06‑19, DF 06‑03, DF 06‑17, DF 06‑20, DF 06‑11, DF 06‑14, DF 06‑01, DF 06‑08, DF 06‑22, and DF 06‑04 lines showed high grain yield. All lines were of semi‑early cycle and of fast cooking. The DF 06‑08 and DF 06‑23 lines showed high calcium concentration in grains (>1.4 g kg‑1 dry matter – DM), and the DF 06‑09, DF 06‑03, DF 06‑04, and DF 06‑06 lines presented high iron concentration in grains (>0.95 g kg‑1 DM) in the two crop cycles. The DF 06‑09 and DF 06‑03 carioca lines present high agronomic performance and high iron concentration in grains. The DF 06‑17 and DF 06‑08 black lines present high agronomic performance and high calcium concentration in grains. The selection of the DF 06‑09, DF 06‑03, DF 06‑17, and DF 06‑08 lines is recommended.